2015
DOI: 10.1186/s12939-015-0246-z
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer care and survival: income and insurance are more predictive in the USA, community primary care physician supply more so in Canada

Abstract: BackgroundOur research group advanced a health insurance theory to explain Canada’s cancer care advantages over America. The late Barbara Starfield theorized that Canada’s greater primary care-orientation also plays a critically protective role. We tested the resultant Starfield-Gorey theory by examining the effects of poverty, health insurance and physician supplies, primary care and specialists, on colon cancer care in Ontario and California.MethodsWe analyzed registry data for people with non-metastasized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…89 Similar to curative treatment barriers observed among those with non-metastasised colon cancer and consistent with this field’s synthetic evidence, 41013 we and others have observed significant barriers to palliative chemotherapy among people living in poverty with metastasised colon cancer. 51415 Furthermore, our analyses found that prevalent health insurance inadequacies in America accounted for most, but not all of the poverty-based chemotherapy inadequacies, whether the intention was to cure or comfort.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…89 Similar to curative treatment barriers observed among those with non-metastasised colon cancer and consistent with this field’s synthetic evidence, 41013 we and others have observed significant barriers to palliative chemotherapy among people living in poverty with metastasised colon cancer. 51415 Furthermore, our analyses found that prevalent health insurance inadequacies in America accounted for most, but not all of the poverty-based chemotherapy inadequacies, whether the intention was to cure or comfort.…”
Section: Introductionsupporting
confidence: 59%
“…10 Among California and Ontario samples, a less stringent PCP supply threshold of 7.5 or more PCPs for every 10 000 community inhabitants was protectively associated with 10-year survival. Consistent with Starfield’s further theorising about the benefits of Canada’s stronger primary care orientation, 31 the protective PCP-survival association was stronger in Ontario than California.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations